PROGNOSTIC FACTORS FOR ORCHIDECTOMY IN TESTICULAR TORSION PATIENTS AT TERTIARY HOSPITAL - Budaya, Taufiq Nur; Daryanto, Besut; Mahandita, I Made (Indonesian Urological Association, 2024)
Objective: This study was conducted to analyze the prognostic factors for orchidectomy in testicular torsion patients. Material & Methods: From January 2001 to December 2021, 100 cases of testicular torsion cases were retrospectively collected. Data were described and analyzed based on clinical factors (age, duration of symptoms, scrotal swelling, high-riding testis, Prehn test, cremasteric reflex, leukocytosis, degree of twisting) and non-clinical factors (distance from hospital, duration of travel to hospital, education level and employment status) for each surgical procedure. Then logistic regression analysis was performed. Results: There were 88 testicular torsion patients (88%) underwent orchidectomy and 12 patients (12%) underwent orchidopexy. There was no significant relationship between age, duration of symptoms, scrotal swelling, Prehn test, cremasteric reflex, leukocytosis, distance from hospital, duration of travel to hospital, education level and employment status with orchidectomy (p>0.05). Significant prognostic factors for orchidectomy in testicular torsion patients were high-riding testis (OR = 0.06; 95% CI = 0.01-0.37; p = 0.002) and degree of twisting (OR = 0.04; 95% CI = 0.006-0.24; p = 0.000). Conclusion: High-riding testis and degree of twisting are prognostic factors for orchidectomy in testicular torsion patients. Keywords: Orchidectomy, prognostic factors, testicular torsion.